Pengaruh Pendidikan, Kesehatan, dan Partisipasi Angkatan Kerja Terhadap Tingkat Kemiskinan di Provinsi Nusa Tenggara Timur (NTT) - Lillah, Neha Galih; Arisetyawan, Kukuh (Jurnal Ekonomika : INDEPENDEN, 2025)
Poverty persists as formidable challenge confronting numerous developing nations, Indonesia included. This inquiry seeks to unravel the extent to which educational attainment, public health conditions, and labor force engagement exert influence upon poverty levels within the province of East Nusa Tenggara (NTT) over the 2019–2023 period. Laboring a numerous paradigm, the study adopted panel data subjected to regression analysis via E-Views 12 software. The empirical evidence delineates that the three independent variables average years of schooling, life expectancy, and labor force participation rate exert a statistically monumental and inverse result on poverty incidence. In essence, the enhancement of educational quality, the fortification of health services, and robust participation in the labor market contribute substantively to poverty alleviation in the region. These findings accentuate the indispensable role of human capital development and employment generation as cornerstones of anti-poverty strategies. It is anticipated that this research may serve as a substantive reference for regional policymakers in crafting interventions that expand educational access, improve healthcare provision, and cultivate inclusive employment opportunities throughout NTT.